2014
DOI: 10.1007/s12639-014-0419-5
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoptic mange infestation in pigs: an overview

Abstract: Sarcoptic mange infestation in pigs is caused by Sarcoptes scabiei var. suis. It is the most common mange infestation of pigs. The parasite is distributed worldwide. Pig owners are generally concerned about the internal parasitic infections and ignored the external parasitic infestations. But the external parasitic infestation with S. scabiei var. suis has economic significance as it causes morbidity, mortality, decreased fertility and feed conversion ratio in pigs. Keeping in view of importance of S. scabies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 40 publications
3
17
0
Order By: Relevance
“…The injuries seen are reddening of the infested area, crusts, hyperkeratosis, and fall of hairs from the area with wrinkled, thickened, rough, raised and thick asbestoslike skin and pruritus. These lesions were similar to those reported by (Das et al, 2010;Laha et al, 2015;OIE, 2016). The observed clinical signs observed in these study were pruritis, as a result, affected pigs showed rubbing of the skin against the wall of the pen, as reported by other authors (Loewenstein et al, 2006;Das et al, 2010;Laha et al, 2015;OIE, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The injuries seen are reddening of the infested area, crusts, hyperkeratosis, and fall of hairs from the area with wrinkled, thickened, rough, raised and thick asbestoslike skin and pruritus. These lesions were similar to those reported by (Das et al, 2010;Laha et al, 2015;OIE, 2016). The observed clinical signs observed in these study were pruritis, as a result, affected pigs showed rubbing of the skin against the wall of the pen, as reported by other authors (Loewenstein et al, 2006;Das et al, 2010;Laha et al, 2015;OIE, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Microscopically the parasites seen appear approximately 500 μm long, with fingerprint-like striations on the cuticle, short and stubby legs, numerous setae and pegs, and with a dorsal patch of tooth-like spines. Treatment carried out was similar to the reports of (Chellapandian et al, 2004;Maiti et al, 2004;Das et al, 2010;Laha et al, 2015;OIE, 2016;Grahofer et al, 2018) who after brushing over the thick scab with wire brush apply Cypermethrin Kumar et al, (2005) then followed by subcutaneous injections of Ivermectin at 300 mg/kg body weight which was repeated after two weeks. The symptoms of pruritis and scratching were disappeared from day 21 posttreatment.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…suis, the mange mite of pigs, causes severe economic losses and frequently serious disease in pigs when untreated [6]. Currently, control of porcine sarcoptic mange relies on the application of acaricides and the maintenance of mite-free herds [18]. Immunity against scabies has been described in different species including humans [43].…”
Section: Background - Vaccines Against Parasitesmentioning
confidence: 99%